CHOSE, ITEM ET DISTINCTION : L'« HOMME VOLANT » D'AVICENNE AVEC ET CONTRE ABŪ HĀŠIM AL-ǦUBBĀ'Ī. Issue 2 (10th August 2018) - Rashed, Marwan
Abstract: This article explores the intimate connection between Avicenna's "flying man" argument and the theory of modes in the school of Abū Hāšim al-Ǧubbā'ī (d. 933). It shows that Avicenna borrows arguments developed originally by Abū Hāšim in order to demonstrate that a definite mode belongs to the living being as a whole ( ǧumla ). He argues for the incorporeality of soul on the basis of this departure from Aristotelian and Neoplatonic psychology and modal ontology. Here one sees Avicenna's subtle engagement with a thinker to whose writings he reacted critically, yet whom he very likely saw as one of the greatest metaphysicians to write in Arabic. Résumé: Cet article se propose de mettre au jour les relations profondes qui existent entre l'argument de l'« homme volant » d'Avicenne et des considérations modales de l'école d'Abū Hāšim al-Ǧubbā'ī (m. 933). Il montre qu'Avicenne réemploie des arguments développés originellement par Abū Hāšim pour démontrer la présence d'un mode de la totalité ( ǧumla ) dans le cas du vivant – argument lui-même opposé à la psychologie aristotélicienne et néoplatonicienne – pour établir, contre l'ontologie modale de ce dernier, la nature incorporelle de l'âme. On voit ainsi se dessiner le jeu subtil d'Avicenne par rapport à celui qu'il avait très probablement identifié, fût-ce à son corps défendant, comme l'un des plus grands métaphysiciens de langue arabe.